Proceedings of the 2nd IEEE/ACM/IFIP International Conference on Hardware/Software Codesign and System Synthesis - CODES+ISSS 2004
DOI: 10.1145/1016720.1016751
|View full text |Cite
|
Sign up to set email alerts
|

Power-performance trade-offs for reconfigurable computing

Abstract: In this paper, we explore the system-level power-performance trade-offs available when implementing streaming embedded applications on fine-grained reconfigurable architectures. We show that an efficient hardware-software partitioning algorithm is required when targeting low-power. However, if the application objective is performance, then we propose the use of dynamically reconfigurable architectures. This work presents a configurationaware data size partitioning approach. We propose a design methodology that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Thus, the PowerPC consumes 259.5 mW and 441 mW of power when clocked at 100 MHz and 300 MHz respectively. These numbers are in close agreement with [15], which also estimates the idle power of the PowerPC to be 50 mW. We obtain all power estimations at an ambient temperature of 25 o C. The highest measured power consumption of our hardware packet classifier is 180 mW when it processes a TCP packet with 100 rules.…”
Section: Power Consumptionsupporting
confidence: 82%
“…Thus, the PowerPC consumes 259.5 mW and 441 mW of power when clocked at 100 MHz and 300 MHz respectively. These numbers are in close agreement with [15], which also estimates the idle power of the PowerPC to be 50 mW. We obtain all power estimations at an ambient temperature of 25 o C. The highest measured power consumption of our hardware packet classifier is 180 mW when it processes a TCP packet with 100 rules.…”
Section: Power Consumptionsupporting
confidence: 82%
“…Numerical data on the significant reconfiguration time for a CLB column confirms observations from previous researchers [4] that execution time for a task operating on a 8 8 block of 8-bit data is orders of magnitude lower than the reconfiguration overhead of such tasks. So, all our schedule length data is for processing a larger block corresponding to a 256 256 color image.…”
Section: Case Study Of Jpeg Encodersupporting
confidence: 79%
“…b) Resource constraints on FPGA: total number of columns being used for task executions and number of columns being reconfigured is limited by the total number of FPGA columns (4) Note that in this constraint we do not explicitly consider the effect of configuration prefetch, where there are columns that have been reconfigured, but not yet executed. Subsequent constraints e) and f) ensure correctness for columns used in configuration prefetch.…”
Section: ) Ilp Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 At the transistor level, Padure et al, 5 have presented interesting results concerning the capacity of Threshold Logic Gate (TLG) circuits to be reconfigured at run time. Past research [7][8][9][10][11] in TLG has shown a significant reduction in the number of transistors required to implement combinatorial and sequential logic.…”
Section: Introductionmentioning
confidence: 99%